An option contract model for leasing containers in the shipping industry - Alejandra Gómez-Padilla; Rosa G. González-Ramírez; Fernando Alarcón; Stefan Voß (Maritime Economics & Logistics, 2020)
We propose an option contract model for the leasing of containers. In an option contract, the shipping company commits to order a quantity of containers from the leasing company and has the right to modify its order at a later stage, according to its actual requirement. Under this scheme, the shipping company is allowed to request a smaller or larger number of containers than the agreed initial order. This is done by buying an option premium in advance from the container leasing company. We present numerical results for different scenarios based on information provided by experts in the industry. For the purposes of comparison, a nonoption contract scheme is also evaluated. According to our numerical results, an option contract is better under a scenario where demand is normally distributed with a large standard deviation. This scenario is commonly observed in practice due to the dynamism and volatility of the shipping industry. We conclude that, under an option contract scheme, the shipping company has more flexibility to adjust its demand for containers and to be requested from the leasing company, and this adjustment is compensated by an option price determined according to variations in demand.
Keywords: 380; Container leasing; Option contracts; Cox–Ross–Rubinstein pricing model; Maritime shipping; Shipping line